Impact of Risk, Corporate Strategy and Capital Structure on Profitability of Nepalese Commercial Banks - Giri, Shreya; Chhetri, Sumita; Shahi, Suraj; Dahal, Yasodha (Nepalese Journal of Business, 2025)
This study examines the impact of risk, corporate strategy and capital structure on the profitability of Nepalese commercial banks. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are credit risk, liquidity risk, annual growth rate of total assets, branch expansion rate, leverage, capital adequacy ratio. The study is based on secondary data of 10 commercial banks with 100 observations for the study period from 2013/14 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of risk, corporate strategy and capital structure on the profitability of Nepalese commercial banks. The study showed that credit risk has a negative impact on return on equity and return on assets. It indicates that increase in credit risk leads to decrease in return on equity and return on assets. Similarly, liquidity risk has a negative impact on return on equity and return on assets and return on assets, indicating that increase in liquidity risk leads to decrease in return on equity and return on assets. Likewise, annual growth rate of total assets has a positive impact on return on equity and return on assets. It indicates that increase in annual growth rate of assets leads to increase in return on equity and return on assets. Similarly, branch expansion rate has a negative impact on return on equity and return on assets. It indicates that increase in branch expansion rate leads to decrease in return on equity and return on assets. Likewise, leverage has a negative impact on return on equity and return on assets. It implies that increase in leverage leads to decrease in return on equity and return on assets. However, capital adequacy ratio has a positive impact on return on equity and return on assets. It indicates that increase in capital adequacy ratio leads to increase in return on equity and return on assets.